The effect of early initiation of antiretroviral therapy in TB/HIV-coinfected patients: A systematic review and meta-analysis - Abay, S; Deribe, K; Reda, A; Biadgilign, S; Datiko, D; Assefa, T; Todd, M; Deribew, A (SAGE Publications, 2015)
Background: The importance of early initiation of antiretroviral therapy (ART) for tuberculosis (TB) and HIV coinfected patients is controversial. We conducted a systematic review and meta-analysis to assess the effect of early initiation of ART (within 2-4 weeks of TB treatment) on several treatment outcomes among TB/HIV coinfected patients. Method: A systematic search of clinical trials was performed in PubMed, Embase, Google Scholar, Science Direct, Medscape, and the Cochrane library. Clinical trials which were published in any language before the last date of search (March 31, 2015) were included. The qualities of the studies were assessed using criteria from the Cochrane Library. Heterogeneity test was conducted to assess the variations among study outcomes. For each study outcome, the risk ratio (RR) with 95% confidence interval (CI) was calculated as a measure of intervention effect. The Mantel-Haenszel method was used to estimate the RR using a fixed-effects model. Findings: A total of 2272 study participants from 6 trials were included in the meta-analysis. Early ART initiation during TB treatment was associated with reduced all-cause mortality (RR = 0.78; 95% CI = 0.63-0.98) and increased rate of TB-associated immune reconstitution inflammatory syndrome (TB-IRIS; RR = 2.19; 95% CI = 1.77- 2.70) and death related to TB-IRIS (RR = 6.94; 95% CI = 1.26-38.22). However, the time of ART initiation has no association with TB cure rate (RR = 0.99; 95% CI = 0.81-1.07), rate of drug toxicity (RR = 1.00; 95% CI = 0.93-1.08), death associated with drug toxicity (RR = 0.40; 95% CI = 0.14- 1.16), rate of low viral load (less than 400 copies/mL; RR = 1.00; 95% CI = 0.96-1.04), and rate of new AIDS-defining illness (RR = 0.84; 95% CI = 0.60-1.18). Immunological response in early ART arms of study participant in different trials showed a greater or equal response compared with late ART arms. Conclusion: This systematic review presents conclusive evidence on the reduction of all-cause mortality as a result of early initiation of ART. However, this study also confirms the high rate of TB-IRIS and death associated with it. Operational and implementation research are required to maintain the benefit of early ART initiation and proper management of TB-IRIS. Studies on the timing of ART in extrapulmonary and multidrug-resistant TB are recommended.